DDRE-49. TRANSIENT OPENING OF THE BLOOD-BRAIN BARRIER BY VASOACTIVE PEPTIDES TO INCREASE CNS DRUG DELIVERY: REALITY VERSUS WISHFUL THINKING?. (12th November 2021) - Smith-Cohn, Matthew; Burley, Nicholas; Grossman, Stuart
Abstract: BACKGROUND: Drug delivery to treat neurologic disease and cancers of the central nervous system (CNS) is severely limited by the blood-brain barrier (BBB). Vasoactive peptides (VAPs) such as regadenoson, adenosine, and labradimil have been shown in animal studies to transiently open the BBB, and regadenoson is currently under investigation in humans to determine if it might improve CNS drug delivery. There is currently limited information regarding the potential for other VAPs to open the BBB transiently. METHODS: We performed a review of the literature evaluating the physiologic effects of vasoactive peptides on the vasculature of the brain and systemic organs. To assess the likelihood that a vasoactive peptide might transiently disrupt the BBB, we devised a four-tier classification system to organize data available in the literature which factors in alterations in BBB integrity and effects on normal brain vasculature and systemic blood vessels. This data was further sorted based on whether it comes from humans, animals, or in vitro systems. RESULTS: We identified 38 VAPs with potential BBB permeability-altering properties. To date, none of these has been shown to open the BBB in humans. Thirteen VAPs increased BBB permeability in rodents. The remaining 25 had favorable physiologic effects on blood vessels but lack specific information on permeability changes to the BBB. We ranked VAPs in a four-tier ranking system related to their known physiologic actions. CONCLUSION: Rodent studies document that analogs of bradykinin and adenosine transiently disrupt the BBB leading to higher chemotherapy concentrations in the CNS. VAPs remain an understudied class of drugs with the potential to increase drug delivery to the CNS. Dozens of VAPs have yet to be formally evaluated for this important clinical effect. This retrospective review summarizes the available data on VAPs highlighting agents that deserve further in vitro and in vivo investigations.